2005
DOI: 10.1189/jlb.0305159
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the CD40-related immunodeficient response in hyper-IgM B cells immortalized with a LMP1-regulated mini-EBV

Abstract: Our previous investigation of a patient (pt1) with non-X-linked hyper-immunoglobulin M syndrome revealed a CD40-mediated defect in B cell activation that resulted in low CD23 expression and absence of germ-line transcription and class-switch recombination. These deficiencies were complemented in vitro by a high threshold of sustained signaling through CD40. To further analyze the signaling defect in pt1 B cells, two types of Epstein-Barr virus lymphoblastoid cell lines (LCLs) were generated that either constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 67 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Because LMP1 activation mimics signals through the CD40 pathway, LCL tet cells allow for independent comparisons of downstream functions in response to regulated LMP1 and CD40 signals. Characterization of these cells revealed a CD23 lo /CD38 hi surface phenotype of generated pt1-LCL tet cells that was distinctly different from the typical CD23 hi / CD38 lo activated phenotype of control LCL tet cells 18 and conventional EBV-immortalized LCLs. 19 We also observed that the pt1-LCL tet cells retained the CD23 lo /CD38 hi phenotype after extended periods of culture with LMP1 or CD40 signals.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because LMP1 activation mimics signals through the CD40 pathway, LCL tet cells allow for independent comparisons of downstream functions in response to regulated LMP1 and CD40 signals. Characterization of these cells revealed a CD23 lo /CD38 hi surface phenotype of generated pt1-LCL tet cells that was distinctly different from the typical CD23 hi / CD38 lo activated phenotype of control LCL tet cells 18 and conventional EBV-immortalized LCLs. 19 We also observed that the pt1-LCL tet cells retained the CD23 lo /CD38 hi phenotype after extended periods of culture with LMP1 or CD40 signals.…”
Section: Introductionmentioning
confidence: 99%
“…One manifestation of the pt1 B-cell defect is uncharacteristically low CD23 expression in the presence of constitutive LMP1 signals 18 ( Figure 1A). To determine whether low CD23 surface expression is due to reduced transcription, pt1-LCL tet and control LCL tet cells were analyzed for CD23a/b expression by qPCR.…”
Section: Diminished Cd23 Expression Is Directly Related To Decreased mentioning
confidence: 99%
See 3 more Smart Citations